Irish intellect: its geographical distribution - Flinn, D. Edgar (Statistical and Social Inquiry Society of Ireland, 1920)
It is difficult when treating of a subject of this nature to estimate who shall be deemed worthy of being included in a list of those who have contributed to Ireland's roll of fame; and I have again undertaken the task of making an analysis in this direction with some degree of hesitation, thoroughly appreciating the difficulties that attach to it, and feeling that to draw a hard and fast line as to who might or who might not be considered to be a person of eminence would be arbitrary and presumptive.
Read 16th April, 1920
Keywords: Irish intellect; Famous Irishmen; 314.15